Telling the truth : the Gospel as tragedy, comedy, and fairy tale - Buechner, Frederick, 1926-2022. (San Francisco : Harper & Row, 1977)
Gift of Union Presby. Church Sustain Trust Fund.
Includes bibliographical references.
Keywords: Preaching; Communication -- Religious aspects -- Christianity